1996
DOI: 10.1089/hum.1996.7.12-1465
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Advanced CNS Malignancies with the Recombinant Adenovirus H5.010RSVTK: A Phase I Trial. University of Pennsylvania Medical Center, Philadelphia

Abstract: Primary CNS malignancies are responsible for approximately 12,000 deaths annually in the United States. There has been little change in the outcome for adults with malignant brain tumors over the past few decades, despite improvements in surgical techniques and advances in radiation therapy. These tumors are uniformly fatal one to two years after diagnosis. The morbidity and mortality of this disease arise from the effects of a locally invasive, non-metastasizing lesion. The patients may suffer from seizures, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(54 citation statements)
references
References 45 publications
1
52
0
1
Order By: Relevance
“…Two prototypic viruses, adenovirus serotypes 2 and 5, have been the most extensively characterized biochemically and genetically and, thus, have been widely used in gene therapy and recombinant vaccination trials. [11][12][13][14][15] While these viruses have demonstrated the ability to be potent vectors with promising futures, data concerning their efficiency in transferring genetic material into intestinal epithelial cells are quite limited and somewhat speculative. [16][17][18][19] We have also experienced similar difficulties as in vivo and in vitro transduction studies suggest that, as enterocytes differentiate, Ad 5 transduction efficiency significantly decreases.…”
Section: Introductionmentioning
confidence: 99%
“…Two prototypic viruses, adenovirus serotypes 2 and 5, have been the most extensively characterized biochemically and genetically and, thus, have been widely used in gene therapy and recombinant vaccination trials. [11][12][13][14][15] While these viruses have demonstrated the ability to be potent vectors with promising futures, data concerning their efficiency in transferring genetic material into intestinal epithelial cells are quite limited and somewhat speculative. [16][17][18][19] We have also experienced similar difficulties as in vivo and in vitro transduction studies suggest that, as enterocytes differentiate, Ad 5 transduction efficiency significantly decreases.…”
Section: Introductionmentioning
confidence: 99%
“…19 Clinical trials assessing the feasibility and adverse side effect of RAds delivering HSV1 -TK for the treatment of GBM have started. 3,8,11 Thirteen patients, nine of whom were diagnosed with GBM, were subjected to a single injection of RAd expressing HSV1 -TK under the control of the Rous sarcoma virus promoter into an intratumoral site, followed by GCV treatment. 8 The study found that the vector dose was safe when the dose did not exceed 2Â10 11 viral particles.…”
Section: Discussionmentioning
confidence: 99%
“…Total resection is difficult due to the lack of a defined tumor edge and nonapparent infiltration into normal brain tissue. 3 The failure of chemotherapy at present is thought to be due to inadequate drug delivery and the development of drugresistant tumor cells. 4 Gene therapy has been proposed as another tool for the treatment of GBM and could prove to be a useful method of delivering therapeutic proteins to precise areas of the brain.…”
Section: G Lioblastoma Multiforme ( Gbm ) Is the Most Commonmentioning
confidence: 99%
“…Furthermore, adenoviral vectors expressing herpes TK driven by constitutive promoters have shown promising efficiencies both in vitro and in animals, 22,23 and a clinical trial using AdHS-VTK in patients with CNS malignancies has been initiated. 24 Although studies by Dewey et al 25 showed growth inhibition of syngeneic glioma after intratumoral injection of an adenoviral vector expressing HSV-TK (AdHS-VTK) in combination with systemic GCV treatment, these investigators also observed active inflammation in the brain 3 months after injection of recombinant AdHSVTK. The use of an astrocyte-specific promoter could possibly reduce the host's immune response in the CNS to the transgene, as suggested by studies using intrahepatic injection of adenoviral vectors.…”
Section: Discussionmentioning
confidence: 99%